Flow Field Simulation for High Speed Train Gearbox - YANG Zhongkun; MIAO Bingrong; ZHANG Xiaoxia; WANG Mingyue (机车电传动)
Regarding the gearbox of a certain type high speed train as the research object, the simulation and analysis of the complex internal flow field during its normal operation was carried out. Three-dimensional model of the gearbox oil lubrication was built, and its internal flow field was calculated by using professional fluid simulation software Pumplinx. The pressure field and velocity field of different instantaneous in the box body were analyzed, and the distribution and variation law of the internal fluid in the normal working of the gear box were summarized. The research results showed that the pressure of the gearbox increased with the increase of the running speed, and the maximum pressure appeared in the gear meshing position; speed fluctuated with time and finally tends to stable, and the maximum speed appeared in the vicinity of the gear tooth top.